Mulberry Leaf Regulates Differentially Expressed Genes in Diabetic Mice Liver Based on RNA-Seq Analysis - Ge, Qi; Zhang, Shu; Chen, Liang; Tang, Min; Liu, Lanlan; Kang, Mengna; Gao, Lu; Ma, Shangshang; Yang, Yanhua; Lv, Peng; Kong, Ming; Yao, Qin; et al. (Frontiers in Physiology, 2018)
The pathogenesis of diabetes mellitus is a complicated process involving much gene regulation. The molecular mechanism of mulberry (Morus alba L.) leaf in the treatment of diabetes is not fully understood. In this study, we used the Illumina HiSeq TM 2500 platform to explore the liver transcriptome of normal mice, STZ-induced diabetic mice, and mulberry leaf-treated diabetic mice, and we obtained 52542956, 52626414, and 52780196 clean reads, respectively. We identified differentially expressed genes (DEGs) during the pathogenesis of diabetes in mice. The functional properties of DEGs were characterized by comparison with the GO and KEGG databases, and the results show that DEGs are mainly involved in the metabolic pathway. qRT-PCR was used to analyze 27 differential genes involved in liver expression in different groups of diabetic mice. Among the DEGs, the expression of Scube1, Spns3, Ly6a, Igf2, and other genes between the control (C) and diabetic control (DC) groups was significantly upregulated; the expression of Grb10, Mup2, and Fasn was significantly downregulated; the expression of the Sqle, Lss, and Irs2 genes between the C group and diabetic group treated with mulberry (DD) was significantly upregulated; the expression of Fabp2, Ly6a, and Grb10 was significantly downregulated; and the expression of Sqle and Lss was significantly upregulated in the DC and DD groups, but Tap1, Igf2, and Spns3 were significantly downregulated. The results of Western blot validation showed that dynamic changes in proteins, such as IGF2, Ly6a, Grb10, and UBD, occurred to regulate the incidence of diabetes by influencing the insulin receptor substrate (IRS) signaling pathway.